Дискусійні питання ранньої історії Смоленська (до проблеми києво-смоленських відносин IX—XIII ст.) - Писаренко, Ю.Г. (Археологія, 1991)
Розглянемо одне з головних питань — про локалізацію населеного пункту, який, за джерелами, вже у IX—X ст. називався Смоленськом. Рассматриваются спорные вопросы ранней истории Смоленска, представляющие важность в контексте темы киево-смоленских отношений, а также истории пути «из Варяг в Греки» — главной государственной магистрали Руси.
Несмотря на узость и противоречивость источников, можно сделать следующие выводы о начальной истории Смоленска. Древнейший Смоленск существовал на месте Гнездовского
археологического комплекса. По наличию керамики, сходной с роменской, и арабских монет первого периода обращения его возникновение может быть отнесено приблизительно к началу IX в. Центр славянской колонизации Гнездово—Смоленск в дальнейшем становится племенным центром кривичей и важнейшим пунктом, контролирующим верхний участок пути «из Варяг в Греки». Мнение о том, что Гнездово было основано норманнами во второй половине IX в. с целью продвижения на Волгу — неубедительно.
С появлением Рюрика в Новгороде в 870 г. территории кривичского племенного союза начинают выходить из-под власти Киева. Киевский князь Аскольд отстаивает свои позиции в Верхнем Поднепровье и Подвинье. Главным предметом борьбы между Новгородом и Киевом, вероятно, становится стратегически важный Смоленск. Мирная передача Смоленска Олегу в 882 г. завершила воссоединение племенного союза кривичей и знаменовала начало объединения Руси. Disputable problems of the early history of Smolensk are considered which are important in the context of the subject of Kiev-Smolensk relations as well as the history of the path «from Varangians to Greeks», the basic state main of the Rus.
Notwithstanding the narrowness and discrepancy of sources, the following conclusions about the initial history of Smolensk may be drawn. The oldest Smolensk existed in the place of Gnezdovian archaeological complex. The origin of the latter may be referred approximately to the beginning of the 9th cent., which is shown by pottery similar to the Romny one and Arabian coins of the first period of circulation. The centre of Slavonic colonization Gnezdovo-Smolensk became later a tribal centre of Krivichi and the most important point controlling the upper section of the path «from Varangians to Greeks». The opinion that Gnezdovo was founded by Northmans in the second half of the 9th century with the .aim to move towards the Volga is unconvincing.
When Ryurik appeared in Novgorod in 870 the territories of the krivichi tribal union left the Kiev’s dominion. Kiev Prince Askold upholded his own stands in the Upper Dnieper area and the Dvina area. Strategically important Smolensk had probably became the main object of struggle between Novgorod and Kiev. Peaceful transfer of Smolensk to Oleg in 882 completed reunification of the tribal union of krivichi and signified an onset of the Rus unification.